Collagen‐coated nano‐electrospun PCL seeded with human endometrial stem cells for skin tissue engineering applications. Issue 4 (9th August 2017) - Sharif, Shiva; Ai, Jafar; Azami, Mahmoud; Verdi, Javad; Atlasi, Mohammad Ali; Shirian, Sadegh; Samadikuchaksaraei, Ali
Abstract: Human endometrial stem cells (hEnSCs) are known as an attractive source of stem cells for regenerative medicine. hEnSCs are easily isolated and are capable of repairing uterine through their strong ability of creating new capillaries. In this study, a three‐dimensional (3D) nanofibrous polycaprolactone (PCL)/collagen scaffold was fabricated and characterized in order to be applied as a new approach for skin reconstruction. Furthermore, the behavior of hEnSCs on this scaffold was investigated. First, a PCL 3D scaffold was constructed using electrospinning technique. Plasma treated and PCL was grafted by collagen. The constructs were characterized for mechanical and structural properties. Cell attachment, proliferation, viability, and differentiation of hEnSCs were assessed after being seeded on PCL and PCL/collagen scaffolds using scanning electron microscopy, 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide, and real‐time polymerase chain reaction tests. The results showed higher wettability for the PCL/collagen scaffold with desirable mechanical and structural characteristics compared to PCL and collagen alone. The attachment and proliferation rates of hEnSCs on the PCL/collagen scaffold were higher compared to those on the bare PCL. Hence, hEnSCs are newly discovered stem cell source for skin tissue engineering in vitro, particularly when developed on PCL/collagen nanofiber scaffolds. Therefore, application of hEnSCs for skin regeneration is a novel therapeutic approach for temporary skin substitute. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 1578–1586, 2018.